The Position of Subject Clauses in the History of English - Javier Rivas (Miscelánea: A Journal of English and American Studies, 2000)
In English, subject clauses can occur either preverbally (in-subject initial position) or postverbally (in final position). In order to account for these structures, linguistic theory has presented two major hypotheses: extraposition and intraposition. All through the history of English, the criterion of frequency seems to support the hypothesis of intraposition, since preverbal subject clauses are not found in OE and are a very marginal type in both the ME and eModE periods. The aim of this paper is to account for the factors which favour the occurrence of preverbal subject clauses by examining the evidence attested in the earlier periods of the English language as well as presenting new data concerning the 18th century. The general tendency is for clauses of this type to convey low informational load, sometimes even acting as cohesive links between paragraphs. Other conditioning factors are the text-type and the principle of end-weight.